RETRACTED: Comparison of the effects of EGF, FGF-b, and NGF on the proliferation, migration, and reprogramming of primary rat Müller cells - Liao, Yanying; Wu, Miaoqin (Frontiers in Cellular Neuroscience, 2024)
Purpose: During the healing process of full-thickness macular holes (FTMHs), the closure and recovery of the hole depend on the migration, proliferation, and activation of Müller cells to promote the closure of holes and restoration of the photosensitive layer. In this study, we investigated the ability of the epidermal growth factor (EGF), fibroblast growth factor-basic (FGF-b), and nerve growth factor (NGF) to influence this process by regulating proliferation, migration, and reprogramming of primary rat Müller cells. Methods: Cell proliferation was measured using a CCK8 [2- (2-Methoxy-4-nitrophenyl)-3- (4-nitrophenyl)-5- (2,4-disulfophenyl)-2H-tetrazolium Sodium Salt] colorimetric assays and EdU [5-Ethynyl-2’-deoxyuridine] assays over 48 hours. Cell migration was measured by scratch-wound assays and transwell migration assays over 48 hours. In addition, we conducted western blot assays and immunofluorescence assays on cells that were specially treated for 1, 3, and 5 days for cell reprogramming. The percentage of EdU-positive cells in Nestin-positive have also been tested by Co-immunofluorescence (Co-IF) staining. Results: EGF and FGF-b significantly promoted the proliferation of Müller cells (P <0.05) at a concentration of 0-50 ng/ml, but NGF did not (P >0.05), compared to untreated controls. Exogenous FGF-b and EGF promote the reprogramming of primary rat Müller cells, significantly enhancing the neural stem cell marker Nestin after stimulation on the first day, third, andfifth days, respectively. The expression of Müller cell marker Vimentin was significantly (P <0.05) reduced during this period compared to the control group. However, there was no significant difference between the NGF group and the control group. Furthermore, the EGF group expressed stronger Nestin expression than the SCM group. The Co-IF staining showed early 50% of activated cells came from newly proliferating cells on the fifth day. Conclusion: These observations indicate that FGF-b can promote the activation of Müller cells in a short time, and enhance the possessive features of neural stem cells, and EGF might act for a longer time. This may have further understanding for growth factors therapy in the treatment of FTMHs and Müller glia might be candidates for cell replacement therapy.